Pulmonary atresia, "intact ventricular septum", and aortopulmonary collateral arteries. - Mildner, R. J. (1997)
In muscular pulmonary atresia, major aortopulmonary collateral arteries are characteristic of pulmonary atresia with ventricular septal defect and are rarely seen in pulmonary atresia with intact ventricular septum. Two unusual cases of muscular pulmonary atresia are reported, one with an intact septum and one with a perimembranous ventricular septal defect, closed in utero by aneurysmal tricuspid tissue. In both cases the pulmonary blood supply came entirely from aortopulmonary collaterals. In case 1 a collateral artery connected the left subclavian artery and hypoplastic pulmonary arteries, and several aortopulmonary collaterals arose from the descending aorta, without overlap between these two circulations. In case 2 the pulmonary trunk and arterial duct were absent and the pulmonary blood supply came entirely from collateral arteries. The right ventricle was of normal size and tripartite with a closed perimembranous ventricular septal defect, discovered only at postmortem examination. These observations suggest right ventricular outflow tract obstruction early in fetal development, with involution of the pulmonary trunk and sixth arch derivatives, and persistence of primitive aortopulmonary connections. The morphology in case 1 is at odds with the theoretical division of pulmonary atresia with intact septum and pulmonary atresia with ventricular septal defect into two separate pathological entities that occur at different stages in fetal development.